Kinematics of lumbar spine motion in rowing during a fatiguing protocol: a comparison of ergometer and boat rowing. Issue 4 (27th March 2011) - Wilson, F; Simms, C; Gormley, J; Gissane, C
Abstract : Background: The incidence of lumbar spine injury is high. Ergometer rowing and fatigue have been cited as risk factors for this injury. Objective: Compare the kinematics of the lumbar spine in rowers on an ergometer and a sculling boat during a fatiguing protocol. Design: Lumbar spine kinematics were assessed in the sagittal plane using a twin axis electrogoniometer. Setting: A laboratory and field based study of elite level rowing. Participants: 19 male rowers, mean age 24.2 (3.7) years, mean weight 82.5 (8.4) kg and height 1.88 (0.05) m. Assessment of risk factors: Maximum range of lumbar flexion was measured before each test. Sagittal plane lumbar spine angular kinematics were measured during an ergometer rowing trial which comprised of an incremental 'step test' on a Concept 2 ergometer. The trial was repeated in a sculling boat on the water. Main outcome measurements: Pre-test maximum flexion and maximum lumbar flexion during each test were compared. Mean sagittal flexion in the lumbar spine during the first and last stage of the step test was compared. The findings of ergometer and boat rowing were compared. Results: Maximum sagittal flexion was 113% (15.2) of pre-test range during ergometer rowing and 104.1% (10.2) during boat rowing. Lumbar flexion increased over the course of testing. Increase in lumbar flexion was significantly greater on the ergometer (mean change+4.4°(0.85)) compared with the boat (mean change+1.3°(1.1)), (mean difference 3.1, 95% CI 0.3 to 5.9, t=2.28, p=0.035). Conclusion: Rowers experience a very high level of lumbar spine flexion which increases over the course of a rowing trial. Ergometer rowing results in significantly greater increases in sagittal motion in the lumbar spine compared to boat rowing.